Wednesday

April 23, 2014

April 23, 2014

Posted by **devon** on Wednesday, May 16, 2012 at 10:47pm.

- math -
**MathMate**, Wednesday, May 16, 2012 at 10:59pmMultiply them out using the FOIL rule.

When you get i², replace by -1.

Using FOIL:

F=1

O=-5i

I=3i

L=-15i²=15

Sum like terms:

(1+3i)(1-5i) = 16-2i

**Related Questions**

math - Simplify: (1+i)/(2-i) A)(1/3)+(2/3i) B)(1/5)+(2/5i) C)(1/3)+(i) D)(1/5)+(...

Algebra - Simplify: (1+i)/(2-i) A)(1/3)+(2/3i) B)(1/5)+(2/5i) C)(1/3)+(i) D)(1/5...

Calc. Help - Simplify. #1. 5(2-i) - 3(4+3i) ..my work: 10-5i-12-9i -2-14i Do you...

Math- Algebra II - Simplify (7-3i)^2. So would I do this: (7-3i) (7-3i) then ...

algebra - Can someone assist help me with the following? Simplify the expression...

Pre Calculus - Simplify 2(3-i^14)- (5-i^23) 3-i Simplify: (5-3i)^2 16+30i ...

Math - For i = the square root of -1, if 3i (2 + 5i) = x + 6i, then x = ? A. –15...

Algebra II (check) - Assume that no denominator equals 0. 2+i/1-3i = 2+i/1-3i...

algebra II - write the sum or difference in the standard form a+bi (2-3i)+(6+5i...

Algebra - Simplify: Write answers in the form of a + bi, where a and b are real ...